The Contribution Of Arm Strength Training To Javelin Throwing Skills In Male Students In Grade XI At MTS Pancasila, Bengkulu City - Syahrul Jaman; Dwingki Marta Putra; Asnawati Asnawati (Journal of Education, 2026)
This study aims to see the contribution of arm muscle strength training to javelin throwing skills in male students of grade XI at MTS Pancasila, Bengkulu City. This type of research is Correlation research. The sample of the study was 20 people. The instruments used in this study were arm muscle strength tests (Pull up) and javelin throwing tests. The results of the javelin throwing skills test without arm muscle strength training and the javelin throwing skills test after doing arm muscle strength training obtained rtable of 0.443 because the correlation coefficient between rxy = 0.89 > 0.443 and an influence of 78.78% which means that with the discovery of the contribution of arm muscle strength training to javelin throwing skills in male students of grade XI at MTS Pancasila, Bengkulu City, then training with the arm muscle strength method can be used to improve javelin throwing skills in male students of grade XI at MTS Pancasila, Bengkulu City.